2020
DOI: 10.1108/emjb-10-2019-0130
|View full text |Cite
|
Sign up to set email alerts
|

Sport, media and actual consumption behavior: an examination of spectator motives and constraints for sport media consumption

Abstract: PurposeThe present study is an initial attempt to assess the impact of motivators and constraints on individual's intention for sport media consumption. The advancement of sport media consumption has been underlined by the academic literature during the past few years. In fact, one of the most conspicuous concerns that experts in the sport industry face nowadays is the fans' preference to stay home and watch sport events. The objective of this research is to determine the impact of motivations and constraints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…For example, Lai et al ( 2013 ) investigated Chinese tourists' intention to visit the USA, and they found that travel constraints negatively influenced travel intention. In addition, Koronios et al ( 2020 ) state that only structural and intrapersonal constraints negatively affect sport spectators' consumption intention, and interpersonal constraints do not significantly influence consumption intention. However, Lee et al ( 2012 ) conclude that there is no significant correlation between constraints and travel intention in disabled tourism market.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lai et al ( 2013 ) investigated Chinese tourists' intention to visit the USA, and they found that travel constraints negatively influenced travel intention. In addition, Koronios et al ( 2020 ) state that only structural and intrapersonal constraints negatively affect sport spectators' consumption intention, and interpersonal constraints do not significantly influence consumption intention. However, Lee et al ( 2012 ) conclude that there is no significant correlation between constraints and travel intention in disabled tourism market.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Based on previous studies examining the relationship between constraints and behavioral intention, it is argued that constraints negatively influence travel intention (Karl et al, 2020 ; Lai et al, 2013 ; Park et al, 2017 ). Among all the constraints, it is found that individuals do not necessarily encounter interpersonal constraints (Koronios et al, 2020 ), especially when they are truly interested in travel (Bonn et al, 2016 ; Gilbert & Hudson, 2000 ; Lai et al, 2013 ; Mei & Lantai, 2018 ). In fact, the solo travel market had been steadily growing before the pandemic (Seow & Brown, 2018 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, those who are involved in SMEs' growth and development would be motivated to use SMM only if they feel the tools are useful and not hazardous in their applicability. Therefore, SMEs make decisions regarding the use of SMM only when they evaluate their applicability as conducive [16][17][18]. Such reservations are supported by the construct of technology acceptance model (TAM) [19] and are not studied yet in the context of SMEs operating in emerging economies that use social media marketing (SMM) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Misinformation and fake news severely affect business activities and innovation with misguidance (Di Domenico et al, 2021 ). Misinformation and fake news interrupt the production chain, leading to considerable fluctuations and disruptions, resulting in uncertainty in the supply chain process (Koronios et al, 2020 ; Petit et al, 2019 ). This uncertainty is perceived to affect the organizations’ supply chain agility and adaptability (Sodhi & Tang, 2020 ).…”
Section: Theoretical Underpinning and Development Of Hypothesesmentioning
confidence: 99%